2003
DOI: 10.1177/154411130301400106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Stimulation of Maxillofacial Bone Healing

Abstract: A substantial part of the maxillofacial surgery practice deals with maxillofacial bone healing. In the past decades, low-intensity ultrasound treatment has been shown to reduce the healing time of fresh fractures of the extremities up to 38%, and to heal delayed and non-unions up to 90% and 83%, respectively. Based on the assumption that the process of bone healing in the bones of the extremities and maxillofacial skeleton is essentially the same, the potential of ultrasound to stimulate maxillofacial bone hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 67 publications
(107 reference statements)
0
44
0
4
Order By: Relevance
“…An investigation by Hollander (1972) using pulsed ultrasound of high frequency showed no adverse effects of any kind but Mannor et al (1972) using continuous ultrasound in the same frequency range observed increased rates of malformations, fetal resorption and low birth weight, thus, pointing to hyperthermia as the most probable teratogenic mechanism. Ultrasound is absorbed by tissues and converted into heat energy (Schortinghuis et al, 2003). Heating effects are the results of the absorption of ultrasound energy from an ultrasound beam (Gent, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation by Hollander (1972) using pulsed ultrasound of high frequency showed no adverse effects of any kind but Mannor et al (1972) using continuous ultrasound in the same frequency range observed increased rates of malformations, fetal resorption and low birth weight, thus, pointing to hyperthermia as the most probable teratogenic mechanism. Ultrasound is absorbed by tissues and converted into heat energy (Schortinghuis et al, 2003). Heating effects are the results of the absorption of ultrasound energy from an ultrasound beam (Gent, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain this discrepancy because of the complicated interaction between the micromechanical forces of ultrasound and the bone healing process. In previous studies concerning mandibular bone defect healing in rats, no effect of daily 20 min ultrasound on bone defect healing could be observed [18][19][20]22 . Ultrasound may stimulate the endochondral ossification process in the extremities, but not the intramembranous ossification process present in the mand- ible.…”
Section: Discussionmentioning
confidence: 99%
“…17 The area of the mandibular teeth was chosen, and the treatment effect was evaluated using spiral CT.…”
Section: Low-intensity Ultrasound Therapymentioning
confidence: 99%